Caribbean Report 15-07-1988 - Crosskill, Hugh (anchor); Whitehorne, Pat (correspondent); Todd-James, Olive (interviewee); Renton, Timothy (interviewee); Hann, Colin (interviewee); Morgan, James (correspondent); Bevan, Edward (correspondent) (The British Broadcasting Corporation, 1988)
This edition of Caribbean Report highlights several issues related to race relations in Britain. The broad-ranging issues covered include racial profiling and questionable practices in the war against drug trafficking, racial discrimination in the real estate market, assertions that Jesus Christ was black, and even questions regarding race and prowess in some types of athletics and sport, just to name a few. The program ends with highlights of the test match between the West Indies and Glamorgan at Swansea.
1. Headlines: Jamaican woman strip-searched at London airport; Firm of London estate agents found guilty of racial bias; Coach Roger Harper happy with West Indies draw with Glamorgan. (00:07-- 00:32)
2. A Jamaican woman who resides in America was strip-searched and also subjected to a ‘cavity’ search at a London airport. Customs officials claim that she was searched because she was suspected of carrying drugs. The traumatized woman, Olive Todd-James, noted that despite producing a letter from her doctors stating that she had recently undergone abdominal surgery, and the fact that she was menstruating at the time, she still had to undergo an invasive body search. She also claims that she has written several complaint letters, including letters to the Queen and to Margaret Thatcher, and has not received and apology. BBC correspondent Pat Whitehorn also spoke with Timothy Renton, Minister of State at the Home Office regarding the incident. Mr. Renton concluded that customs officials may have had good reason for their actions, and advised that Mrs. Todd-James should ask her Member of Parliament take up the matter. The MP for Tottenham where Mrs. Todd-James’ sister lives has taken up the matter, and has sent a letter to the Prime Minister, requesting a full investigation. (00:38-04:12)
3. The Richard Barclay Agency, a London firm of real estate agents, has been found guilty of crude racial stereotyping. This has occurred amidst fears that the rapid growth in private sector housing could encourage racial segregation. The Commission for Racial Equality (CRE) found that the agency had refused to show properties to Asians, and quotes one staff member as saying that “Asians are deceitful, neighbours would not like the smell of curry and the agency would lose credibility.” BBC correspondent Hugh Crosskill asks the CRE’s Housing Officer Colin Hann what action would be taken against the agency in light of this finding of guilt. Mr. Hann notes that a non-discrimination notice has been issued against the agency, which means that the CRE would have the right to monitor their activities for five years. It also means that tests would be carried out to determine whether equal treatment is meted out to both black and white people. With the British government changing its housing policy and seeking to sell a lot of its properties to the private sector, Crosskill asks Hann whether he was concerned about this. Hann notes that he was concerned about the private sector’s lack of accountability, and how it could be monitored. He also cited racial harassment as another area of concern. Crosskill asked whether the racial bias was limited to Asians, and Hann replied that it was not. He also noted that the discrimination occurred at the level of the sellers, the owners and the neighbours. (04:20-06:59)
4. Financial News: Jerry Timmins reports. This segment includes commentary from BBC economic correspondent James Morgan. (07:10-08:48)
Keywords: Drug control -- Great Britain.; Racial profiling in law enforcement -- Great Britain.; Race discrimination -- Great Britain.; Great Britain -- Race relations.; Discrimination in housing -- Great Britain.; Test matches (Cricket) -- Great Britain.